The Language of Deception: Exploring the Linguistic Strategies and Etiquette of Philanderers in Managing Infidelity - Brandon N. Obenza; Angel Mae M. Pontillo (International Journal of Education and Humanities, 2025)
This study explores the linguistic conventions and etiquette used by philanderers—people who commit infidelity and extramarital affairs. Using a multiple case study approach, this study focuses on the language characteristics of philanderers, mainly how they use rhetorical techniques and linguistic strategies to manage various relationships and to conceal and disguise such activity. Through in-depth interviews and analyses of mobile communication, this research demonstrates varied use of language, vocabulary, deceiving tactics, and coded terminology. The study displays a common practice of employing prudent vocabulary choices, the tone used in conversation, politeness in language and communication, and reassuring techniques to manipulate emotion and persuasion. The use of code words, deceiving language, coded terminologies for meeting places and sexual activities, and selective language used inside social circles have been indicated in the results as part of the participants’ linguistic patterns. Furthermore, philanderers use various techniques in preserving and hiding relationships, such as employing intimate and seductive language, adaptive language, creative expression, emotionally appealing expressions, and respectful and polite language. By revealing the adept linguistic strategies and patterns of the philanderers,  this study contributes to a broader knowledge of how language and communication are used in dealing with deceit and trust in relationships and provides practical insights into determining linguistically deceiving expressions. This research offers a deeper understanding of how philanderers navigate their lives and manage multiple relationships by carefully and consciously selecting language and communication, which can be valuable in various professional and personal contexts. This study provides new avenues for comprehending the complex dynamics of multiple relationships and the role of linguistics and language